2020
DOI: 10.1090/proc/14948
|View full text |Cite
|
Sign up to set email alerts
|

A note on the consistency operator

Abstract: It is a well known empirical observation that natural axiomatic theories are pre-well-ordered by consistency strength. For any natural theory T , the next strongest natural theory is T`Con T . We formulate and prove a statement to the effect that the consistency operator is the weakest natural way to uniformly extend axiomatic theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…We will explore the analogy between the recursion-theoretic and proof-theoretic well-ordering phenomena throughout this paper. On the one hand, we will describe proof-theoretic theorems from [22,23,24,33] whose statements and proofs were inspired by this recursion-theoretic research. On the other hand, we will also describe purely recursion-theoretic results from [19] that were inspired by the aforementioned proof-theoretic theorems.…”
Section: Turing Degree Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…We will explore the analogy between the recursion-theoretic and proof-theoretic well-ordering phenomena throughout this paper. On the one hand, we will describe proof-theoretic theorems from [22,23,24,33] whose statements and proofs were inspired by this recursion-theoretic research. On the other hand, we will also describe purely recursion-theoretic results from [19] that were inspired by the aforementioned proof-theoretic theorems.…”
Section: Turing Degree Theorymentioning
confidence: 99%
“…In [33] some limitative results on the scope of this approach are established. In particular, it is shown that the assumption that g is recursive is necessary in the statement of Theorem 8.6.…”
Section: Analogues Of Martin's Conjecturementioning
confidence: 99%
See 1 more Smart Citation
“…In [4,6] an approach to this problem was proposed. The approach in question was inspired by Martin's approach to an analogous question in recursion theory: Why are the natural Turing degrees well-ordered by Turing reducibility?…”
Section: Introductionmentioning
confidence: 99%
“…Roughly speaking, Martin's Conjecture says that the only definable degree-invariant functions, up to Martin-equivalence, are the constant functions, the identity function, and the iterates of the Turing jump. 1 The optimistic proposal in [4,6] was that an analogue of Martin's Conjecture holds for axiomatic theories. Let's fix a sound recursively extension T of elementary 1 Of course, the notion of "definable" is left vague in what I have written.…”
Section: Introductionmentioning
confidence: 99%